Unlocking the IPO Potential: Insights from International Markets with Established Pathways for SMEs Going Public - Sherzod Botirjonov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article explores the intricacies of small and medium-sized enterprises (SMEs) going public through initial public offerings (IPOs), drawing insights from international markets renowned for their established pathways. By examining the regulatory frameworks, market conditions, and support systems in key jurisdictions such as the United States, United Kingdom, and European Union, the article highlights commonalities and differences that influence the IPO process for SMEs.